Quantitative spatial analysis of Colombian continental wetlands transformation - Patiño, Jorge E (Biota Colombiana, 2016)
Wetlands are among the most productive ecosystems in the world, but its importance is not yet widely recognized. Although these ecosystems are constantly subject to natural changes, human activity has accelerated change rates significantly and it is estimated that more than half the area of wetlands in the world was lost during the last century. This trend was verified in Colombia and almost a quarter of wetlands surface has been converted to other land covers. Using spatial data and quantitative methods, this study quantifies the transformation of wetland areas in the country, identifies the drivers of this transformation and explores the association with other socioeconomic factors. Results indicate that cattle raising and agriculture are the main drivers of wetland change in the country, and to a lesser extent mining, urbanization, and infrastructure. The relationships of wetland transformation with change drivers vary throughout the territory, which should be considered for wetland management and conservation policies in the country.